Characterization of semiconductor materials : principles and methods - McGuire, G. E. (Noyes Publications, 1989)
Includes chapters on Electrical Characterization, Ion Mass Spectrometry, Photoelectron Spectroscopy, and Ion/Solid Interactions.
Keywords: Semiconductors -- Handbooks, manuals, etc.; elektronické knihy; electronic books